Peran Pemimpin Rohani Gembala dalam Memelihara dan Menggembalakan Jemaat - Tambunan, Tanjung; Sinaga, Janes; Lusiana Sinambela, Juita (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
his study aims to analyze the role of pastoral care through stewardship in the context of the pastor's duties and responsibilities towards the congregation. Stewardship as a pastoral concept can make a significant contribution to the growth of faith and the quality of life of the congregation, as well as strengthening the relationship between the pastor and the congregation. This study uses a descriptive qualitative method to identify the role of pastors in stewardship. Limitations in measuring the effectiveness of stewardship, especially the long-term impact on the growth of faith and the quality of life of the congregation, are challenges in this study. This study suggests increasing the involvement of the congregation in stewardship through providing an active role, which will help them grow in faith and Christian life. Practical implications that can be applied include the importance of a personal approach in pastoral care, such as more frequent personal meetings between pastors and congregations. The results of the study indicate that pastoral care through stewardship has a positive impact on the growth of faith andthe quality of life of the congregation, as well as strengthening the relationship between pastors and congregations and increasing the effectiveness of pastoral care.